Ceremonial and etiquette in viceregal processions at Santafe - Robert Ojeda Pérez (Universitas Humanística, 2011)
This paper stems from a reflection on Norbert Elias’ The court society. The aim is to identify the symbols and signs allowing to think that there were people striving to establish a courtier society in viceregal Santafe de Bogotá, beginning with the deployment of fine manners, ceremonial and etiquette in social events, like parades performed in the event of new viceroy appointments.